Fresh cut fruit salads as a promising vehicle for Lactobacillus acidophilus and Lactobacillus plantarum - Martins, E. M.F.; Ramos, A. M.; Stringheta, P. C.; Lago-Vanzela, E. S. [UNESP]; Oliveira, P. M.; Martins, M. L. (My University, 2017)
This work aimed to study the potential use of fresh cut fruit salads as carriers for Lactobacillus acidophilus LA-5 and Lactobacillus plantarum. The viability of L. acidophilus LA-5 and L. plantarum in fruit salads was above 7.83 Log CFU/g during 120 h of storage. Scanning electron microscopy showed that the fruit tissues served as shelter for probiotic bacteria. These tissues allowed bacterial adhesion, especially on pineapple, banana, papaya, mango and apple. Fruit salads from different treatments had no differences regarding pH, acidity and °Brix (p > 0.05). L. acidophilus caused changes to apple texture. Fruit salads with L. acidophilus presented psychrotrophic counts of at least 3.0 Log CFU/g less than control fruit salads for up to 120 h of storage at 8°C. L. acidophilus and L. plantarum reduced coliform counts at 30°C in treated fruit salads, improving biopreservation. Therefore, fruit salads have potential for use as promising carriers of probiotic bacteria and could constitute an alternative option for consuming healthy and functional food products.
Keywords: Fruit mix; Functional food; Minimally processed food Probiotic